Alumina ceramic nanofiber and preparation method thereof

By using modified spinning additives and sintering additives, alumina ceramic nanofibers were prepared, which solved the problem of insufficient performance of alumina ceramic nanofibers in the prior art, and achieved the improvement of high heat resistance, thermal insulation and mechanical properties, and was suitable for high-temperature heat insulation materials.

CN119571501APending Publication Date: 2025-03-07JIAXING FREBANG NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411739122.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The heat resistance, thermal insulation and mechanical properties of existing alumina ceramic nanofibers are insufficient, and the dispersion of spinning additives and sintering additives in the preparation process is poor, which affects the performance of the fiber.

Method used

Sodium metaaluminate, modified polyvinyl alcohol and modified polyvinylpyrrolidone were used as spinning additives to prepare alumina ceramic nanofibers through electrospinning and sintering processes, and modified titanium dioxide@manganese dioxide composite materials were used as sintering additives to improve the heat resistance and mechanical properties of the fibers.

Benefits of technology

The heat resistance, thermal insulation and mechanical properties of alumina ceramic nanofibers have been significantly improved, making them suitable for high-temperature thermal insulation materials and have good commercial application value.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of nanofibers, and provides aluminum oxide ceramic nanofibers and a preparation method thereof.The aluminum oxide ceramic nanofibers are prepared from, by weight, 5-15 parts of sodium metaaluminate, 40-60 parts of spinning auxiliaries and 1-4 parts of sintering auxiliaries; wherein the spinning auxiliary agent is prepared from the following raw materials: polyvinyl alcohol, modified polyvinylpyrrolidone and deionized water. The alumina ceramic nanofiber provided by the invention has the characteristics of good heat resistance, heat insulation performance and mechanical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nanofibers, and in particular to an alumina ceramic nanofiber and a preparation method thereof. Background Art

[0002] Alumina ceramic fiber is a new type of high-performance inorganic ceramic fiber. Its main component is aluminum oxide. Compared with non-oxide fibers such as carbon fiber and silicon carbide fiber, it has many excellent properties. It not only has excellent properties such as high modulus, high strength, and high temperature resistance, but also has good high-temperature oxidation resistance, corrosion resistance and electrical insulation. At the same time, alumina ceramic fiber has good surface activity and is easy to be compounded with polymers, metals, and ceramic matrices to form many composite materials with excellent properties. It is also an engineering material with relatively good comprehensive performance. It has very important applications in composite materials, industry, and military fields.

[0003] Nanofiber is a kind of fiber material with extremely fine microstructure, extremely high specific surface area and special mechanical properties. The use of nanofibers to prepare thermal insulation materials has become a hot topic in current research. Among them, alumina ceramic nanofibers have the characteristics of low thermal conductivity, small thermal expansion coefficient, and good thermal shock resistance. They can significantly reduce heat loss and can be used as good high-temperature thermal insulation materials.

[0004] The traditional method for preparing inorganic fibers is to heat the raw materials to make them molten and then melt-spin them. However, the melting point of alumina is very high, and even when melted, its melt viscosity is very low, which makes it difficult to prepare its fibers by the melt method. Therefore, people have studied and developed a process of first preparing a precursor solution and then performing electrospinning and sintering to prepare alumina ceramic nanofibers. However, this process still has some unresolved defects. For example, commonly used spinning aids are polyvinyl pyrrolidone and polyvinyl alcohol, which may have the disadvantage of insufficient high temperature resistance; and the sintering aids added during calcination may have the problem of poor dispersion. These defects will affect the heat resistance and mechanical properties of the prepared alumina ceramic nanofibers.

[0005] Patent CN 117364292A discloses a method for preparing fine-grained dense alumina ceramic fibers. The invention first prepares aluminum sol, iron sol, PVP solution, and acidified silica sol, and then mixes them in a set ratio to obtain a mixed sol, and concentrates the mixed sol to obtain a spinnable gel. The spinnable gel is pre-sintered and microwave-sintered after spinning to obtain fine-grained dense alumina ceramic fibers, which have the advantages of fine grains, dense microstructure, and high tensile strength. However, the application does not take into account the temperature resistance of PVP, and the fiber may have poor stability after long-term use.

[0006] Therefore, there is an urgent need in the market for an alumina ceramic nanofiber with good heat resistance, thermal insulation and mechanical properties. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention uses sodium aluminate, a spinning aid and a sintering aid as main raw materials to synthesize an alumina ceramic nanofiber with good heat resistance, heat insulation and mechanical properties.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] In one aspect, the present invention provides an alumina ceramic nanofiber, which comprises the following raw materials by weight: 5-15 parts of sodium aluminate, 40-60 parts of a spinning aid, and 1-4 parts of a sintering aid;

[0010] Wherein, the spinning aid comprises the following raw materials: polyvinyl alcohol, modified polyvinyl pyrrolidone, and deionized water.

[0011] In some embodiments of the present invention, the preparation of the spinning aid comprises the following steps:

[0012] Add polyvinyl alcohol and modified polyvinyl pyrrolidone into deionized water, and stir at 75-85° C. for 4-6 hours to obtain a spinning aid.

[0013] In some embodiments of the present invention, the mass ratio of the polyvinyl alcohol to the modified polyvinyl pyrrolidone is 1:(0.08-0.12).

[0014] Preferably, the mass ratio of the polyvinyl alcohol to the modified polyvinyl pyrrolidone is 1:0.1.

[0015] The applicant chose to use polyvinyl alcohol and polyvinyl pyrrolidone as the main components of the spinning aid. Polyvinyl alcohol is a water-soluble polymer compound with good film-forming and adhesion properties. However, polyvinyl alcohol that has not been specially treated may contain a certain amount of metal ions, which will affect the spinning effect to a certain extent. Polyvinyl pyrrolidone has dual functional groups of carbonyl and imino groups, which can preferentially complex high-valent metal ions, thereby improving the spinnability of polyvinyl alcohol. The applicant controls the ratio and concentration of polyvinyl alcohol and polyvinyl pyrrolidone to make the spinning aid have better uniformity and stability, thereby improving the mechanical properties and thermal insulation properties of alumina ceramic nanofibers.

[0016] In some embodiments of the present invention, the method for preparing the modified polyvinyl pyrrolidone comprises the following steps:

[0017] Add polybenzimidazole and polyvinyl pyrrolidone into N, N-dimethylacetamide, stir at 70-80°C for 23-25h, vacuum degass, wash and dry to obtain modified polyvinyl pyrrolidone.

[0018] Wherein, the polyvinyl pyrrolidone is PVPK30.

[0019] In some embodiments of the present invention, the mass ratio of polyvinyl pyrrolidone to polybenzimidazole is 1:(0.5-0.7).

[0020] Preferably, the mass ratio of polyvinyl pyrrolidone to polybenzimidazole is 1:0.6.

[0021] Polyvinyl pyrrolidone has been widely used in electrospinning technology due to its good biocompatibility, solubility, film-forming properties and amphiphilicity. It is often used as the main component of spinning aids. However, polyvinyl pyrrolidone has the defect of being sensitive to heat, which may lead to a decrease in the overall performance of the spinning aid.

[0022] On the one hand, the applicant selected polyvinyl pyrrolidone PVPK30 with a specific molecular weight as the main body, which has good dispersibility and dispersion stability, probably because the polyvinyl pyrrolidone with this molecular weight can be used as a stabilization mechanism in the form of steric hindrance; on the other hand, the applicant used polybenzimidazole to modify polyvinyl pyrrolidone. The benzene ring and imidazole repeating units in the polybenzimidazole molecular chain can make the modified polyvinyl pyrrolidone have higher thermal stability, oxidation resistance and mechanical properties, thereby improving the overall heat resistance, thermal insulation and mechanical properties of the spinning aid.

[0023] In some embodiments of the present invention, the method for preparing the sintering aid comprises the following steps:

[0024] 1) adding tetrabutyl titanate to ammonia water, stirring and then adding to a reaction vessel, performing a hydrothermal reaction at 170-190° C., cooling to room temperature, adding hexadecyltrimethylammonium bromide, stirring, centrifuging, washing, and drying to obtain modified titanium dioxide for later use;

[0025] 2) KH550 and ethanol aqueous solution are mixed, stirred, the modified titanium dioxide of step 1) is added, ultrasonicated, heated to 65-75° C., refluxed, washed, dried, added to 0.05-0.15 mol / L potassium permanganate aqueous solution, ultrasonicated, filtered, washed, dried, and a sintering aid is obtained.

[0026] Wherein, in the step 2), the mass ratio of modified titanium dioxide to KH550 is 1:(1-1.5).

[0027] Preferably, in step 2), the mass ratio of modified titanium dioxide to KH550 is 1:1.25.

[0028] In some embodiments of the present invention, in step 1), the mass ratio of tetrabutyl titanate to hexadecyltrimethylammonium bromide is 1:(0.4-0.6).

[0029] Preferably, in step 1), the mass ratio of tetrabutyl titanate to hexadecyltrimethylammonium bromide is 1:0.5.

[0030] In some embodiments of the present invention, in step 2), the mass ratio of modified titanium dioxide to potassium permanganate aqueous solution is 1:(7-8).

[0031] Preferably, in step 2), the mass ratio of modified titanium dioxide to potassium permanganate aqueous solution is 1:7.5.

[0032] It is crucial to add a certain amount of sintering aids during the preparation of ceramic nanofibers, which can promote sintering densification and improve the performance of fiber materials. Among them, titanium dioxide and manganese dioxide, as variable-valence metal oxides, can activate the lattice by producing solid solutions and reduce the sintering temperature, and can be used as sintering aids. However, titanium dioxide has the problem of poor dispersibility, and the combination of the two may have the hidden danger of insufficient stability. These problems will affect the mechanical properties and heat resistance of the prepared alumina ceramic nanofibers.

[0033] The applicant first used tetrabutyl titanate as a titanium source and ammonia water as a reaction medium, controlled the hydrothermal conditions to 170-190°C, and selected hexadecyltrimethylammonium bromide as a modifier to prepare a modified titanium dioxide with good dispersibility; further, the applicant subjected the synthesized modified titanium dioxide to a surface treatment with a silane coupling agent KH550, and then immersed it in an aqueous potassium permanganate solution for ultrasonic dispersion modification to obtain a modified titanium dioxide @ manganese dioxide composite material as a sintering aid. The core-modified titanium dioxide dispersed the distribution of manganese dioxide on the surface of the microspheres and improved the overall stability of the sintering aid, so that the sintering aid can play a better role, thereby improving the mechanical properties and heat resistance of the alumina ceramic nanofibers.

[0034] Another aspect of the present invention further provides a method for preparing the alumina ceramic nanofibers described in the above technical solution, comprising the following steps:

[0035] S1. Add sodium aluminate to the spinning aid and stir for 2-4 hours to obtain a precursor solution for standby use;

[0036] S2. After electrospinning the precursor solution of step S1, place it in a 40-50°C environment for 30-60 minutes, add a sintering aid, heat it to 450-550°C, keep it warm for 50-70 minutes, sinter it at 1300-1400°C for 1-2 hours, and cool it to room temperature to obtain alumina ceramic nanofibers.

[0037] In some embodiments of the present invention, in step S2, the temperature of electrospinning is 15-25°C, the humidity is 35-45%, the output voltage is 18-22 kV, the propulsion speed of the propulsion pump is 0.5-0.7 mL / h, and the receiving distance is 11-13 cm.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The present invention uses sodium aluminate, a spinning aid and a sintering aid as main raw materials to synthesize an alumina ceramic nanofiber. Through the synergistic effect of the various components, the alumina ceramic nanofiber has good heat resistance, thermal insulation and mechanical properties.

[0040] (2) The present invention selects polyvinyl alcohol and polyvinyl pyrrolidone as the main components of the spinning aid, controls the molecular weight of polyvinyl pyrrolidone and modifies it, so as to improve the heat resistance of the spinning aid, thereby improving the overall heat resistance, thermal insulation and mechanical properties of the spinning aid.

[0041] (3) The present invention synthesizes a modified titanium dioxide @ manganese dioxide composite material as a sintering aid, which improves the dispersibility and overall stability of the sintering aid, thereby improving the mechanical properties and heat resistance of the alumina ceramic nanofibers.

[0042] (4) The alumina ceramic nanofibers prepared in the present invention have high heat resistance, thermal insulation and mechanical properties, can be widely used in the field of thermal insulation materials, and have good commercial application value. DETAILED DESCRIPTION

[0043] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0044] In the following examples and comparative examples, except for modified polyvinyl pyrrolidone and sintering aids, the other compound monomers and related reagents used can be purchased from the market, among which polyvinyl alcohol was purchased from Dongguan Chengjin Plastic Chemical Co., Ltd.; polyvinyl pyrrolidone was PVPK30, purchased from Huzhou Shenhua Polymer Materials Co., Ltd.; polybenzimidazole was purchased from Dongguan Dongli Plastic Raw Materials Co., Ltd.

[0045] Preparation Example 1

[0046] The synthetic method of modified polyvinyl pyrrolidone A comprises the following steps:

[0047] 18 g of polybenzimidazole and 30 g of polyvinyl pyrrolidone were added to 50 g of N, N-dimethylacetamide, stirred at 75° C. for 24 h, vacuum degassed, washed with deionized water for 3 times, and dried at 105° C. for 12 h to obtain modified polyvinyl pyrrolidone A.

[0048] Preparation Example 2

[0049] The specific implementation method of modified polyvinyl pyrrolidone B is the same as that of modified polyvinyl pyrrolidone A, except that the mass of polybenzimidazole is replaced with 12g.

[0050] Preparation Example 3

[0051] The synthesis method of sintering aid A comprises the following steps:

[0052] 1) 8 g of tetrabutyl titanate was added to 70 ml of 6.5 mol / L ammonia water, stirred for 30 min, then added to a reaction vessel lined with polytetrafluoroethylene, and hydrothermally reacted at 180° C. for 8 h, cooled to room temperature, and 4 g of hexadecyltrimethylammonium bromide was added, stirred for 30 min, centrifuged, washed with anhydrous ethanol and deionized water three times in sequence, and dried at 80° C. for 8 h to obtain modified titanium dioxide for standby use;

[0053] 2) 5 g of KH550 and 40 g of 80 wt% ethanol aqueous solution were mixed, stirred for 30 min, 4 g of modified titanium dioxide prepared in step 1) was added, ultrasonicated for 10 min, heated to 70° C., refluxed for 2 h, washed with anhydrous ethanol and deionized water three times in sequence, dried at 80° C. for 12 h, added to 30 g of 0.1 mol / L potassium permanganate aqueous solution, ultrasonicated for 30 min, filtered, washed with deionized water until colorless and transparent, and dried at 80° C. for 12 h to obtain sintering aid A.

[0054] Preparation Example 4

[0055] The specific implementation manner of the sintering aid B is the same as that of the sintering aid A, except that in step 1), the mass of hexadecyltrimethylammonium bromide is replaced with 2.5 g.

[0056] Preparation Example 5

[0057] The specific implementation manner of sintering aid C is the same as that of sintering aid A, except that in step 2), the mass of potassium permanganate aqueous solution is replaced with 34 g.

[0058] Example 1

[0059] An alumina ceramic nanofiber, which comprises the following raw materials by weight: 10 parts of sodium aluminate, 50 parts of a spinning aid, and 2.5 parts of a sintering aid A;

[0060] The preparation of the spinning aid comprises the following steps:

[0061] 20 g of polyvinyl alcohol and 2 g of modified polyvinyl pyrrolidone A were added into 200 ml of deionized water and stirred at 80° C. for 5 h to obtain a spinning aid.

[0062] The preparation method of alumina ceramic nanofibers in this embodiment includes the following steps:

[0063] S1. Add sodium aluminate to the spinning aid and stir for 3 hours to obtain a precursor solution for standby use;

[0064] S2, electrospinning the precursor solution of step S1, placing it in a 45°C environment for 45 minutes, adding sintering aid A, heating to 500°C, keeping the temperature for 60 minutes, sintering at 1350°C for 1.5 hours, and cooling to room temperature to obtain alumina ceramic nanofibers.

[0065] The temperature of the electrospinning was 20°C, the humidity was 40%, the output voltage was 20 kV, the propulsion speed of the propulsion pump was 0.6 mL / h, and the receiving distance was 12 cm.

[0066] Example 2

[0067] An alumina ceramic nanofiber, which comprises the following raw materials by weight: 5 parts of sodium aluminate, 40 parts of a spinning aid, and 2.5 parts of a sintering aid A;

[0068] The preparation of the spinning aid comprises the following steps:

[0069] 20 g of polyvinyl alcohol and 1.6 g of modified polyvinyl pyrrolidone A were added into 200 ml of deionized water and stirred at 75° C. for 6 h to obtain a spinning aid.

[0070] The preparation method of alumina ceramic nanofibers in this embodiment includes the following steps:

[0071] S1. Add sodium aluminate to the spinning aid and stir for 2 hours to obtain a precursor solution for standby use;

[0072] S2, electrospinning the precursor solution of step S1, placing it in a 40°C environment for 60 minutes, adding sintering aid A, heating to 450°C, keeping the temperature for 50 minutes, sintering at 1300°C for 2 hours, and cooling to room temperature to obtain alumina ceramic nanofibers.

[0073] The electrospinning temperature was 15°C, the humidity was 35%, the output voltage was 18 kV, the propulsion speed of the propulsion pump was 0.5 mL / h, and the receiving distance was 11 cm.

[0074] Example 3

[0075] An alumina ceramic nanofiber, which comprises the following raw materials by weight: 15 parts of sodium aluminate, 60 parts of a spinning aid, and 2.5 parts of a sintering aid A;

[0076] The preparation of the spinning aid comprises the following steps:

[0077] 20 g of polyvinyl alcohol and 2.4 g of modified polyvinyl pyrrolidone A were added into 200 ml of deionized water and stirred at 85° C. for 4 h to obtain a spinning aid.

[0078] The preparation method of alumina ceramic nanofibers in this embodiment includes the following steps:

[0079] S1. Add sodium aluminate to the spinning aid and stir for 4 hours to obtain a precursor solution for standby use;

[0080] S2, electrospinning the precursor solution of step S1, placing it in a 50°C environment for 30 minutes, adding sintering aid A, heating to 550°C, keeping the temperature for 50 minutes, sintering at 1400°C for 1 hour, and cooling to room temperature to obtain alumina ceramic nanofibers.

[0081] The temperature of the electrospinning was 25°C, the humidity was 45%, the output voltage was 22 kV, the propulsion speed of the propulsion pump was 0.7 mL / h, and the receiving distance was 13 cm.

[0082] Example 4

[0083] An alumina ceramic nanofiber, which comprises the following raw materials by weight: 12 parts of sodium aluminate, 60 parts of a spinning aid, and 3 parts of a sintering aid A;

[0084] Wherein, the spinning aid is the same as that in Example 1.

[0085] The preparation method of alumina ceramic nanofibers in this embodiment is the same as that in Example 1.

[0086] Example 5

[0087] An alumina ceramic nanofiber, which comprises the following raw materials by weight: 7 parts of sodium aluminate, 40 parts of a spinning aid, and 2 parts of a sintering aid A;

[0088] Wherein, the spinning aid is the same as that in Example 1.

[0089] The preparation method of alumina ceramic nanofibers in this embodiment is the same as that in Example 1.

[0090] Example 6

[0091] This embodiment provides an alumina ceramic nanofiber and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the mass of modified polyvinyl pyrrolidone A in the preparation process of the spinning aid is 1.2 g.

[0092] Example 7

[0093] This embodiment provides an alumina ceramic nanofiber and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that modified polyvinyl pyrrolidone A is replaced by modified polyvinyl pyrrolidone B in equal amounts.

[0094] Example 8

[0095] This embodiment provides an alumina ceramic nanofiber and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the sintering aid A is replaced by an equal amount of sintering aid B.

[0096] Example 9

[0097] This embodiment provides an alumina ceramic nanofiber and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the sintering aid A is replaced by an equal amount of a sintering aid C.

[0098] Example 10

[0099] This embodiment provides an alumina ceramic nanofiber and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of titanium dioxide is used to replace the sintering aid A.

[0100] Embodiment 11

[0101] This embodiment provides an alumina ceramic nanofiber and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of manganese dioxide is used to replace the sintering aid A.

[0102] Comparative Example 1

[0103] This comparative example provides an alumina ceramic nanofiber and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that polyvinyl pyrrolidone is used in an equal amount to replace modified polyvinyl pyrrolidone A.

[0104] Performance Testing

[0105] The heat resistance, thermal insulation and mechanical properties of the alumina ceramic nanofibers of Examples 1-11 and Comparative Example 1 were tested, and the test results are shown in Table 1.

[0106] (1) Thermal insulation performance

[0107] The thermal insulation performance is judged by testing the thermal conductivity at 900℃, with reference to standard YB / T 4130-2005.

[0108] (2) Heat resistance and mechanical properties

[0109] The ceramic nanofibers were subjected to tensile testing using a tensile testing machine. The samples were clamped by a fixture at 25°C and tested. The samples were long strips with a length of 150 mm, a width of 10 mm, and a gauge length of 50 mm.

[0110] The tensile strength of the ceramic nanofibers at 800°C was tested under the above conditions to determine the heat resistance. The smaller the decrease in tensile strength, the better the heat resistance.

[0111] Table 1

[0112] Group Thermal conductivity (W / m·k) Tensile strength, 25℃(MPa) Tensile strength, 800℃(MPa) Example 1 0.023 4.30 4.23 Example 2 0.025 4.25 4.18 Example 3 0.027 4.20 4.10 Example 4 0.024 4.23 4.15 Example 5 0.024 4.22 4.13 Example 6 0.035 3.96 3.70 Example 7 0.036 3.93 3.65 Example 8 0.038 3.76 3.52 Example 9 0.040 3.55 3.31 Example 10 0.050 3.11 2.85 Embodiment 11 0.052 3.05 2.67 Comparative Example 1 0.045 3.20 3.00

[0113] It can be seen from the data in Table 1 that the alumina ceramic nanofibers in Examples 1-5 of the present invention have good heat resistance, thermal insulation and mechanical properties as a whole. Among them, Examples 6-7 respectively changed the ratio between polyvinyl alcohol and modified polyvinyl pyrrolidone in the spinning aid and the ratio between polybenzimidazole and polyvinyl pyrrolidone in the synthesis process of modified polyvinyl pyrrolidone, so that the heat resistance of modified polyvinyl pyrrolidone was not well improved and the synergistic performance between polyvinyl alcohol and modified polyvinyl pyrrolidone decreased, which led to the decrease of heat resistance, thermal insulation and mechanical properties of alumina ceramic nanofibers; Examples 8-9 changed the ratio between the key components in the synthesis of sintering aids, so that the dispersibility of the sintering aids was not well improved, which led to the decrease of heat resistance, thermal insulation and mechanical properties of alumina ceramic nanofibers; Examples 10-11 and Comparative Example 1 respectively selected titanium dioxide, manganese dioxide and polyvinyl pyrrolidone to replace sintering aid A and modified polyvinyl pyrrolidone A in equal amounts. Tests found that the heat resistance, thermal insulation and mechanical properties of alumina ceramic nanofibers all showed poor results.

[0114] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. An alumina ceramic nanofiber, characterized in that: The alumina ceramic nanofibers include the following raw materials by weight: 5-15 parts of sodium aluminate, 40-60 parts of spinning aids, and 1-4 parts of sintering aids; Wherein, the spinning aid comprises the following raw materials: polyvinyl alcohol, modified polyvinyl pyrrolidone, and deionized water.

2. The alumina ceramic nanofiber according to claim 1, characterized in that: The preparation of the spinning aid comprises the following steps: Add polyvinyl alcohol and modified polyvinyl pyrrolidone into deionized water, and stir at 75-85° C. for 4-6 hours to obtain a spinning aid.

3. The alumina ceramic nanofiber according to claim 2, characterized in that: The mass ratio of the polyvinyl alcohol to the modified polyvinyl pyrrolidone is 1:(0.08-0.12).

4. The alumina ceramic nanofiber according to claim 1, characterized in that: The preparation method of the modified polyvinyl pyrrolidone comprises the following steps: Add polybenzimidazole and polyvinyl pyrrolidone into N, N-dimethylacetamide, stir at 70-80°C for 23-25h, vacuum degass, wash and dry to obtain modified polyvinyl pyrrolidone.

5. The alumina ceramic nanofiber according to claim 4, characterized in that: The mass ratio of the polyvinyl pyrrolidone to the polybenzimidazole is 1:(0.5-0.7).

6. The alumina ceramic nanofiber according to claim 1, characterized in that: The preparation method of the sintering aid comprises the following steps: 1) adding tetrabutyl titanate to ammonia water, stirring and then adding to a reaction vessel, performing a hydrothermal reaction at 170-190° C., cooling to room temperature, adding hexadecyltrimethylammonium bromide, stirring, centrifuging, washing, and drying to obtain modified titanium dioxide for later use; 2) KH550 and ethanol aqueous solution are mixed, stirred, the modified titanium dioxide of step 1) is added, ultrasonicated, heated to 65-75° C., refluxed, washed, dried, added to 0.05-0.15 mol / L potassium permanganate aqueous solution, ultrasonicated, filtered, washed, dried, and a sintering aid is obtained.

7. The alumina ceramic nanofiber according to claim 6, characterized in that: In the step 1), the mass ratio of tetrabutyl titanate to hexadecyltrimethylammonium bromide is 1:(0.4-0.6).

8. The alumina ceramic nanofiber according to claim 6, characterized in that: In the step 2), the mass ratio of modified titanium dioxide to potassium permanganate aqueous solution is 1:(7-8).

9. A method for preparing alumina ceramic nanofibers according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Add sodium aluminate to the spinning aid and stir for 2-4 hours to obtain a precursor solution for standby use; S2. After electrospinning the precursor solution of step S1, place it in a 40-50°C environment for 30-60 minutes, add a sintering aid, heat it to 450-550°C, keep it warm for 50-70 minutes, sinter it at 1300-1400°C for 1-2 hours, and cool it to room temperature to obtain alumina ceramic nanofibers.

10. The method for preparing alumina ceramic nanofibers according to claim 9, characterized in that: In step S2, the temperature of the electrospinning is 15-25° C., the humidity is 35-45%, the output voltage is 18-22 kV, the propulsion speed of the propulsion pump is 0.5-0.7 mL / h, and the receiving distance is 11-13 cm.

Citation Information

Patent Citations

  • Preparation method of fine-grain compact alumina ceramic fiber

    CN117364292A